Analysis and Modeling of Depolarization Effects in Mueller Matrix Spectroscopic Ellipsometry Data. (2016) - Halagačka, L.; Postava, K.; Pištora, J.
Abstract: In this paper we present importance of depolarization effects modeling to fit spectroscopic Mueller matrix ellipsometry data. The relevant theoretical background based on Mueller matrix formalism is presented. The sample of SiO2 layer (approx. 1 μm thick) on silicon substrate is used to demonstrate depolarization effects in obtained experimental data. In the first step the presence of interferences in the layer is used for modeling of depolarization effects caused by finite spectral resolution of the Mueller matrix ellipsometer. In the next step the depolarization caused by focusing of the probe light is analyzed and modeled. Both finite spectral resolution and beam focusing is a common issue in the optical characterization of samples with lateral dimensions smaller than (commonly used) collimated beam. Therefore to fit experimental data with model it is important to assume those depolarization effect into model.